2020
DOI: 10.1161/hypertensionaha.119.14556
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Cardiac ASK1 (Apoptosis Signal-Regulating Kinase 1) Controls p38-MAPK (Mitogen-Activated Protein Kinase) and Orchestrates Cardiac Remodeling to Hypertension

Abstract: Systemic hypertension increases cardiac workload causing cardiomyocyte hypertrophy and increased cardiac fibrosis. An underlying feature is increased production of reactive oxygen species. Redox-sensitive ASK1 (apoptosis signal-regulating kinase 1) activates stress-regulated protein kinases (p38-MAPK [mitogen-activated protein kinases] and JNKs [c-Jun N-terminal kinases]) and promotes fibrosis in various tissues. Here, we determined the specificity of ASK1 signaling in the heart, with the hypothesis that ASK1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 40 publications
4
61
0
Order By: Relevance
“…Separate minipumps were used for AngII and dabrafenib delivery. Minipumps were incubated overnight in sterile PBS (37°C), then implanted subcutaneously under continuous inhalation anaesthesia using isoflurane (induction at 5%, maintenance at 2–2.5%) mixed with 2 l/min O 2 , as previously described [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Separate minipumps were used for AngII and dabrafenib delivery. Minipumps were incubated overnight in sterile PBS (37°C), then implanted subcutaneously under continuous inhalation anaesthesia using isoflurane (induction at 5%, maintenance at 2–2.5%) mixed with 2 l/min O 2 , as previously described [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Echocardiography was performed with a Vevo 2100 imaging system using a MS400 18-38 MHz transducer (Visualsonics) as previously described [ 22 ]. Left ventricular cardiac dimensions were assessed from short axis M-mode images with the axis placed at the mid-level of the left ventricle at the level of the papillary muscles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summing up the results of existing studies, we can learn that several proteins are involved in regulating the progression of high blood pressure, such as endothelin-1, Rac1, and G protein-coupled estrogen receptor [ 30 – 32 ], but hypertension-related genes have not been identified systemically. Here, we revealed that 2186 DE-mRNAs (including 1312 up-regulated mRNAs and 874 down-regulated mRNAs) were discovered in hypertensive mice.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a striking enrichment in cEVs of antioxidants, including Cat, Sod1/2/3, Gpx1/3/4/7/8, Gstm1/2/5, Gsta3/4. Tight regulation of redox signalling is central to cardiac physiology (ion channels, contraction) and pathology (fibrosis, hypertrophy), whereby excess oxidants, such as reactive oxygen species (ROS), result in oxidative stress, cell damage and cardiac pathologies [94][95][96]. While EVs have been shown to deliver functional antioxidant enzymes between cells (fibroblasts and hepatic cells [97,98]), and particularly in the heart to reduce oxidative stress during myocardial infarction [99], whether they regulate antioxidant levels in cardiac physiology remains unknown.…”
Section: Once Blood Has Clearedmentioning
confidence: 99%